5-HT2A receptor dysregulation in a schizophrenia relevant mouse model of NMDA receptor hypofunction - Kazuhito Nakao; Mahendra Singh; Kiran Sapkota; Andrew Fitzgerald; John J. Hablitz; Kazu Nakazawa (Translational Psychiatry, 2022)
Abstract Blockade of N-methyl-D-aspartate receptors (NMDAR) is known to augment cortical serotonin 2A receptors (5-HT2ARs), which is implicated in psychosis. However, the pathways from NMDAR hypofunction to 5-HT2AR up-regulation are unclear. Here we addressed in mice whether genetic deletion of the indispensable NMDAR-subunit Grin1 principally in corticolimbic parvalbumin-positive fast-spiking interneurons, could up-regulate 5-HT2ARs leading to cortical hyper-excitability. First, in vivo local-field potential recording revealed that auditory cortex in Grin1 mutant mice became hyper-excitable upon exposure to acoustic click-train stimuli that release 5-HT in the cortex. This excitability increase was reproduced ex vivo where it consisted of an increased frequency of action potential (AP) firing in layer 2/3 pyramidal neurons of mutant auditory cortex. Application of the 5-HT2AR agonist TCB-2 produced similar results. The effect of click-trains was reversed by the 5-HT2AR antagonist M100907 both in vivo and ex vivo. Increase in AP frequency of pyramidal neurons was also reversed by application of Gαq protein inhibitor BIM-46187 and G protein-gated inwardly-rectifying K+ (GIRK) channel activator ML297. In fast-spiking interneurons, 5-HT2AR activation normally promotes GABA release, contributing to decreased excitability of postsynaptic pyramidal neurons, which was missing in the mutants. Moreover, unlike the controls, the GABAA receptor antagonist (+)-bicuculline had little effect on AP frequency of mutant pyramidal neurons, indicating a disinhibition state. These results suggest that the auditory-induced hyper-excitable state is conferred via GABA release deficits from Grin1-lacking interneurons leading to 5-HT2AR dysregulation and GIRK channel suppression in cortical pyramidal neurons, which could be involved in auditory psychosis.